Ludification de l’enseignement-apprentissage du français (FL1/FLS) : une revue de la portée - Amal Boultif; Béatrice Crettenand Pecorini; Patrick R. Labelle (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This scoping review is part of a global research strategy carried out by a multidisciplinary team from the University of Ottawa interested in the role of games as an educational approach, more specifically here for the identification of pathways of integration of gamified devices to support the teaching-learning of French (FL1 and FLS) for students in grades 4 to 8 (9 to 14 years old). A systematic search strategy was implemented in eight databases, identifying 1848 references published between 2012 and 2022, references imported into Covidence. After removing duplicates, 1540 titles and abstracts were evaluated of which 128 articles were then examined in detail leading to the extraction of 20 articles that were rigorously analyzed with NVivo. Our results indicate that for French teaching through play and game, the notion of pleasure still remains taboo, and digital games are still used sparingly in the classroom. While a playful pedagogy is widely used in kindergarten, as serious games are in the secondary and in higher education, we can notice that it is almost absent between 4th and 8th grades.